2012
DOI: 10.1111/j.1365-2591.2012.02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the frequency and nature of hyaline ring granulomas in inflammatory odontogenic cysts

Abstract: The present results suggest a very low frequency of HRGs in inflammatory odontogenic cysts and support the hypothesis that these structures arise from the implantation of foreign material, most likely food particles of plant or vegetable origin. The diverse microscopic features of HRG possibly represent different developmental stages of this structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
2
11
1
1
Order By: Relevance
“…In contrast to cases of human oral HRG, in which thickened hyaline rings could be observed grossly and which had underwent calcification [3], the hyaline structures in the present case were thin and without calcification. Plant material and hyaline structures were weakly positive for Masson trichrome stain as found in other studies [21, 22]. The findings in the present case suggest that the chronic inflammation was mild and the detected lesions were not at an advanced stage.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to cases of human oral HRG, in which thickened hyaline rings could be observed grossly and which had underwent calcification [3], the hyaline structures in the present case were thin and without calcification. Plant material and hyaline structures were weakly positive for Masson trichrome stain as found in other studies [21, 22]. The findings in the present case suggest that the chronic inflammation was mild and the detected lesions were not at an advanced stage.…”
Section: Discussionsupporting
confidence: 87%
“…Table 1 summarizes 35 publications where the data related to the source of origin, location and diagnosis of 208 cases with OPHRGs has been tabulated and reviewed. [ 1 2 3 4 5 6 10 11 12 13 14 15 16 ] Including a total of 173 patients OPHRGs that were reviewed by Philipsen and Reichart, those reported from 1971 to 2008. [ 5 ] 28 reports favor an exogenous origin, where food particles of plant or vegetable have been considered as source origin in 26 reports.…”
Section: Discussionmentioning
confidence: 99%
“…In oral and maxillofacial region, these lesions often are noted in association with odontogenic and nonodontogenic cysts, but very rarely in odontogenic tumors. [5789101112] Talacko and Radden[7] in their retrospective study, found evidence of PG in periapical lesions and odontogenic cysts which were missed initially at the time of diagnosis. Similarly, Henriques et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Henriques et al . [10] retrospectively studied inflammatory odontogenic cysts and found that 3.3% (22 of 661 cases) of inflammatory cysts were associated with PG. In the majority of cases, the response to foreign body is minimal; hence, it can be missed and which may be reason for underreporting of PG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation